Overview of safety & health cost framework for the construction of rail infrastructure projects / Izatul Farrita Mohd Kamar, Asmalia Che Ahmad and Mohmad Mohamad Derus - Izatul Farrita, Mohd Kamar; Asmalia, Che Ahmad; Mohmad, Mohamad Derus (Universiti Teknologi MARA, Perak, 2017)
The construction of rail infrastructure project is expanding in Malaysia to enhance and integrate the urban public transportation services. This transportation service is one of the National Key Result Areas (NKRA) which is a priority under the Government Transformation Program (ETP). Fatalities, serious injuries and damage to properties occur every year due to rapid construction of this project. Numerous studies have attempted to explain the various losses that could be incurred by companies after the occurrence of an accident. These losses are difficult to isolate, identify and evaluate. Models to analyze and calculate the costs of prevention in the construction industry are limited to apply in this area because they are based on studies carried out in the manufacturing sector. Furthermore, the traditional models for analysing these costs are limited to identifying and classifying them. Therefore, the objectives of this paper are to investigate the overall view of safety and health cost model approaches globally (i.e. UK, Australia, Singapore and Malaysia) and to identify the direction of safety and health cost framework to be practiced in Malaysia.